2021
DOI: 10.1186/s12873-021-00507-2
|View full text |Cite
|
Sign up to set email alerts
|

Examining the association between paramedic transport to the emergency department and hospital admission: a population-based cohort study

Abstract: Background Increasing hospitalization rates present unique challenges to manage limited inpatient bed capacity and services. Transport by paramedics to the emergency department (ED) may influence hospital admission decisions independent of patient need/acuity, though this relationship has not been established. We examined whether mode of transportation to the ED was independently associated with hospital admission. Methods We conducted a retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 22 publications
2
12
0
Order By: Relevance
“…We speculate some of the contributing factors include: difficulty in accessing primary healthcare, a lack of timely access to care, perceived situation by the patient, a sense of superior in-hospital care, and a lack of awareness of other healthcare services [24][25][26]. Consistent with previous literature, we found that older age groups and increasing comorbidities may be contributing factors to increased paramedic utilization [6,27,28].…”
Section: Previous Studies and Reportssupporting
confidence: 87%
See 2 more Smart Citations
“…We speculate some of the contributing factors include: difficulty in accessing primary healthcare, a lack of timely access to care, perceived situation by the patient, a sense of superior in-hospital care, and a lack of awareness of other healthcare services [24][25][26]. Consistent with previous literature, we found that older age groups and increasing comorbidities may be contributing factors to increased paramedic utilization [6,27,28].…”
Section: Previous Studies and Reportssupporting
confidence: 87%
“…Contrary to traditional conceptualizations of paramedicine as an emergency service, the majority of paramedic transported patients have non-emergent medical complaints and conditions [1,6]. Expanding and aligning paramedic scope of practice, clinical decision-making, and models of care with primary care skills and service accessibility may support efforts to improve patient-centered care and lessen the burden of ED workload [1,31].…”
Section: Health Policy and Regulation Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 6-9 In Ontario, ED utilisation by patients with non-emergent conditions has doubled population growth (13.4% vs 6.2%) in the past decade. 6 10 With Ontario's continued population growth, the demand for ED healthcare may continue to increase, further challenging departments to manage already overburdened workloads. [11][12][13] Challenges of ED overcrowding extend beyond Canada; international research reports similar increases in patient volumes and longer admission times.…”
Section: Introductionmentioning
confidence: 99%
“…(1) Empirically, the majority of emergent triaged paramedic transports do not receive emergency medicine in the ED, do not clinically deteriorate, are discharged home directly from the ED (56.6%) and a sizeable proportion receive physician interventions considered primary care-like (39.3%). (3,4) Paramedics transporting high-acuity triaged patients exclusively to the nearest ED constitutes an operational ine ciency; all emergently triaged patients are handled the same in the prehospital setting, independent of patient repatriation for continuity of care, patient preference, ED workload, sta ng, or bed availability. (1) In circumstances where emergently triaged conditions do not require emergency or time-sensitive care, transport to an alternative ED could bene t both the patient and overwhelmed EDs.…”
Section: Introductionmentioning
confidence: 99%